Acurácia de quatro técnicas radiográficas intrabucais na detecção de desadaptação entre implante e componente protético - Darós, Pollyana (2017)
Misfit at implant-abutment joints (IAJ) may compromise the perimplant tissues health. Intraoral radiograph are an complementary diagnostic method to misfit detection and an orthogonal relation between the central beam, the implant, and the radiographic film is indicated. The aim of this study evaluated the accuracy of 4 intraoral radiographic techniques on the detection of gaps at IAJ. Twenty implants were placed in prototyped jaws and UCLA-type abutments with metal collar were installed. Different gaps were simulated by placing one or three 50-μm-thickness polyester strips at the IAJ, and the absence of the strip represented the control group (no gap). Periapical radiographs with different film-holders were taken for each technique: bisecting, interproximal, parallel-cone and modified-parallel-cone (with a custommade paralleling index). A total of 240 digital radiographs were evaluated by 4 specialists in dental implants. The ROC curves (Az) and Fisher’s Exact comparison tests were performed at a significance level of 5%. Diagnostic values (sensitivity, specificity, accuracy, positive, and negative predictive values) were also obtained. The Kappa test was used to assess intra- and inter-evaluator reproducibility, which ranged from substantial to almost perfect, and moderate to substantial, respectively. All diagnostic values were lower for the bisecting technique for both 50- and 150-μm gaps. Az values for the bisecting technique were significantly lower than those obtained for the other 3 techniques (p<.05), which did not differ from each other. The 150-μm gaps were more easily detected than 50-μm gaps only for the bisecting technique (p˂.05). The interproximal, parallel-cone and, modified-parallel-cone techniques were the most accurate to detect misfits at IAJ. The bisecting technique should not be clinically indicated for this purpose.